THE INFLUENCE OF THE D'TALKSHOW BKTV PROGRAM ON AUDIENCE BEHAVIORAL CHANGE: : A Case Study at the Regional Office of the Ministry of Religious Affairs of the Bangka Belitung Islands Province - Yulista, Yera; Handika Maheswara (MEDIOVA: Journal of Islamic Media Studies, 2025)
This study aimed to investigate the influence of broadcast messages from the D’Talkshow program on Babel Kemenag TV (BKTV) on audience behavior change in the Bangka Belitung Islands Province. This program is considered crucial as it serves as a credible information source regarding the Ministry of Religious Affairs' activities, as well as matters of da'wah (Islamic propagation) and diversity.The research adopted a quantitative approach using a survey method, gathering primary data by distributing questionnaires to BKTV’s YouTube subscribers. The collected data was then analyzed using regression analysis and linearity tests.The regression analysis results confirmed that the Program Influence variable (X) significantly affects the Audience Behavior Change variable (Y), demonstrated by a significance value of . This finding concludes that the D’Talkshow program indeed has an impact on the audience. However, the linearity test indicated that no significant linear relationship exists between the two variables, as shown by the Deviation from Linearity Sig. value of.In conclusion, the D’Talkshow program of BKTV is proven to significantly influence audience behavior change, even though the relationship between the program's influence and the audience's behavioral change is not significantly linear.